Implementasi Nilai-nilai Moral dan Agama pada Anak Usia Dini - Rizki Ananda (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
One of the basic attitudes a child must have to be a good and righteous man is to have good moral and religious attitudes and behaviors in behaving like God's people, family members, and community members. Early Childhood Age is the best time for teachers of Early Childhood Education (PAUD) to lay the foundations of moral and religious education to the. Although the role of parents is enormous in establishing the moral and religious foundations of their children, the role of the early childhood teacher is not small in laying down the moral and religious grounds for a child, since usually, the early child tends to follow his teacher's instructions. Therefore, an early childhood teacher should always try in various ways in order to guide early childhood to have a good personality, which is based on moral and religious values. With the foundation of moral and religious education to children of early childhood, an early childhood can learn to distinguish good and bad behavior, right and wrong, and accustomed to run the teachings of religion in accordance with the level of growth and development. Educating PAUD children with good moral and religious education is not an easy task, therefore PAUD teachers should always improve their insight, understanding, and skills related to the development of morals and religion of children in early childhood.